2021
DOI: 10.3390/ijerph181910084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Interventions with Child Domestic Workers: A Rapid Systematic Review

Abstract: Little is known about interventions to support the education, skills training, and health of female child domestic workers (CDWs). This rapid systematic literature review followed PRISMA guidelines (PROSPERO registration: CRD42019148702) and summarises peer-reviewed and grey literature on health, education, and economic interventions for CDWs and interventions targeting employers. We searched six electronic databases and purposively searched grey literature. We included observational studies, which included an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Because these youths work in relative isolation, away from public view, initiatives to address emotional, physical, or sexual abuse and promote healthy child development will have to address the behaviors of employers while identifying the most effective ways to provide support to abused youths. Community-based violence-prevalence interventions that include poverty reduction alongside psycho-social activities in areas where there is a high density of CDWs may have promise [ 61 ]. However, these strategies may also exclude youth who are the least visible and hardest to reach.…”
Section: Implications For Research and Programmingmentioning
confidence: 99%
“…Because these youths work in relative isolation, away from public view, initiatives to address emotional, physical, or sexual abuse and promote healthy child development will have to address the behaviors of employers while identifying the most effective ways to provide support to abused youths. Community-based violence-prevalence interventions that include poverty reduction alongside psycho-social activities in areas where there is a high density of CDWs may have promise [ 61 ]. However, these strategies may also exclude youth who are the least visible and hardest to reach.…”
Section: Implications For Research and Programmingmentioning
confidence: 99%
“…Broadly, there are many more studies of interventions for child marriage than for CDWs. Recent systematic reviews have found just one CDW targeted intervention among five evaluations, compared with 30 quasi-experimental and experimental evaluations targeting child brides [ 16 , 18 ]. There are no studies on disability among CDW, and among child brides, there is insufficient evidence on whether children with disabilities are more or less at risk than those without disabilities [ 19 ].…”
Section: Introductionmentioning
confidence: 99%